Nonviral RNA transfection to transiently modify T cells with chimeric antigen receptors for adoptive therapy - Riet, Tobias; Holzinger, Astrid; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Abken, Hinrich (Synthetic Messenger RNA and Cell Metabolism Modulation, 2013)
Redirecting T cells with a chimeric antigen receptor (CAR) of prede fined specificity showed remarkable ef ficacy in the adoptive therapy trials of malignant diseases. The CAR consists of a single chain fragment of variable region (scFv) antibody targeting domain covalently linked to the CD3 z signalling domain of the T cell receptor complex to mediate T cell activation upon antigen engagement. By using an antibodyderived targeting domain a CAR can potentially redirect T cells towards any target expressed on the cell surface as long as a binding domain is available. Antibody-mediated targeting moreover circumvents MHC restriction of the targeted antigen, thereby broadening the potential of applicability of adoptive T cell therapy. While T cells were so far genetically modi fied by viral transduction, transient modification with a CAR by RNA transfection gained increasing interest during the last years. This chapter focuses on methods to modify human T cells from peripheral blood with a CAR by electroporation of in vitro transcribed RNA and to test modi fied T cells for function for use in adoptive immunotherapy. © Springer Science+Business Media New York 2013.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Adoptive cell therapy; Chimeric antigen receptor; Electroporation; In vitro transcription; RNA; T cell